3D culture of neural progenitor cells in gelatin norbornene (GelNB) hydrogels: mechanical tuning and hypoxia characterization - Dienemann, Sandra; Wohlenberg, Ole Jacob; Gerstenberger, Jan Georg; Lavrentieva, Antonina; Pepelanova, Iliyana (Frontiers in Bioengineering and Biotechnology, 2025)
The development of physiologically relevant three-dimensional (3D) culture platforms for neural stem cell (NSC) cultivation is essential for advancing neuroscience research, disease modelling, and regenerative medicine. In this study, we introduce norbornene-functionalized gelatin (GelNB) hydrogels crosslinked with a laminin-based peptide as a bioactive scaffold for NSC culture. A central composite design of experiments (DoE) approach was employed to systematically map hydrogel mechanical properties across varying macromer (4%–7%) and crosslinker (3–9 mM) concentrations via a response surface. This enabled precise tuning of hydrogel stiffness between 0.5 and 3.5 kPa, closely mimicking the mechanical properties of brain tissue. The optimized GelNB hydrogel formulation (5% GelNB, 8 mM crosslinker) supported NSC viability and enhanced NSC cluster formation demonstrating its suitability for 3D neural cell culture. Furthermore, we characterized the onset of hypoxia in 3D constructs using genetically encoded fluorescent hypoxia biosensors, revealing a cell density-dependent hypoxic response. At 3 × 106 cells/mL, hypoxic response was detected only after 7 days of cultivation, whereas at 8 × 106 cells/mL, hypoxic response was already observed within 24 h, illustrating the importance for using adequate cell numbers to avoid or achieve in situ physiological hypoxia. These findings highlight the importance of controlled ECM properties and oxygen microenvironments in NSC cultivation and provide valuable insights for the development of advanced biomimetic neural tissue models.